Distribution Pattern of Agricultural Zakat in Fulfilling Village Food Security - Husnawiyah; Nurul Widyawati Islami Rahayu; Fauzan (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2025)
Agricultural zakat has a role in strengthening food security in rural areas. However, faced with the challenge of lack of literacy in the distribution of agricultural zakat owned by the community, especially farmers. So that the distribution of agricultural zakat has not contributed to food security in rural areas. Therefore, this research aims to, first; to explore food security in rural areas; Second, to analyze the distribution pattern of agricultural zakat that has been running in rural areas, third, to explore the pattern of distribution of agricultural zakat that can meet village food security. The research was carried out with a qualitative approach, with the type of case study in Pandanarum Village as a representation of the village that was able to produce a watermelon crop of 15 tons per 0.5 hectare. Thus, the object is worth researching. Data was collected by means of observation, interviews and documentation. The data were analyzed using descriptive techniques through the Miles and Huberman interactive model. The data was tested using source triangulation and techniques. This study resulted in findings 1. Food security in rural areas presents challenges such as limited access to food and dependence on the harvest season, thus requiring appropriate interventions to ensure sustainable food availability, 2. The distribution pattern of agricultural zakat in rural areas today generally runs in two forms, direct distribution by muzakki to mustahik and distribution through organized amil zakat institutions, with consumptive and productive methods, 3. The effective distribution pattern of agricultural zakat for village food security is to distribute zakat to the Amil Zakat Institution (LAZ) which is then redistributed to farmers.